Rural Public Cash Desks in System of Financial Relations of Nalchik District in Last Third of 19th — Early 20th Century - A. Kh. Abazov; M. Kh. Berbekova; M. V. Dyshekov (Научный диалог)
On the basis of documentary materials, the features of the functioning of rural (aul) public cash desks (sums) in the Nalchik district of the Terek region in the last third of the 19th — early 20th centuries are considered. The volume of powers and the legal status of rural treasurers responsible for conducting activities on public funds are characterized. The channels of replenishment and expenditure of their funds are identified and the procedure for accounting for funds is analyzed. For this, annual statistical reports on the state of the Nalchik District, statements of receipt and expenditure of funds from public funds, regulations and instructions for the activities of rural treasurers and other officials of rural, district and district governments were studied. The verage age of rural treasurers and candidates for their position is determined. The territorial organization of the functioning of public cash desks in the Nalchik district is characterized. It was established that one public cash desk was created and operated in one settlement. Exceptions to this rule are considered. It is concluded that rural public cash desks were the most important institution of the financial and economic system of the Nalchik District in the last third of the 19th — early 20th centuries, accumulating cash flow at the local level.